2004
DOI: 10.1079/phn2004611
|View full text |Cite
|
Sign up to set email alerts
|

Sources and credibility of nutrition information among black urban South African women, with a focus on messages related to obesity

Abstract: Objectives: (1) To identify the major sources of nutrition information, and the perceived credibility thereof, among urban black South African women; and (2) to determine the level of knowledge regarding nutrition, particularly regarding the topic of obesity. Design: A cross-sectional descriptive study that was both qualitative (focus groups) and quantitative (individual questionnaires). Three hundred and ninety-four black women aged 17 -49 years were conveniently sampled from the Western Cape and Gauteng prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 14 publications
0
72
0
Order By: Relevance
“…Seven were from lower-middle-income countries; four from Morocco (28,(30)(31)(32)38) , two were Kenyan (33,44) and one Ghanaian (34) . Three studies were situated in South Africa; an upper-middle-income country (29,(35)(36)(37)43) .…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven were from lower-middle-income countries; four from Morocco (28,(30)(31)(32)38) , two were Kenyan (33,44) and one Ghanaian (34) . Three studies were situated in South Africa; an upper-middle-income country (29,(35)(36)(37)43) .…”
Section: Search Resultsmentioning
confidence: 99%
“…Nine studies (29)(30)(31)(32)(33)(34)(35)(36)(37)(39)(40)(41)(42)44) reported the effects of individualor household-level determinants (online supplementary material, Supplemental Table 3). …”
Section: Individual-and Household-level Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many South Africans do not know how to choose the right type and quantities of food to satisfy their nutritional requirements (3) . Therefore, there is a need to help South African consumers make better food choices during food purchasing.The food label forms an integral part of the consumers' decision-making processes, as it provides nutritional information that could assist them in making healthy food choices (2,4) . Prior exposure to food labels also limits consumers' information searching and consequently saves them time during food purchase (5) .…”
mentioning
confidence: 99%
“…Furthermore, the study found that the media was a powerful medium to convey scientifically accurate information to the lay public and should be better utilised. [22] The cost of food was identified as the strongest determining factor influencing food choices, regardless of the school quintile. The effect of food cost on food choices and healthy eating cannot be underestimated; it calls for drastic measures to be implemented by the SA government and the food industry to curb the increasing cost of healthy food.…”
Section: Discussionmentioning
confidence: 99%